Gambaran Peran Orang Tua dalam Melindungi Anak Usia Sekolah dari Tindakan Pelecehan Seksual di SDN Sananwetan 02 UPTD Pendidikan Kecamatan Sananwetan Kota Blitar - Ryan Budianto (Journal of Ners and Midwifery, 2016)
Children sex abuse is an immoral act done to the children under age such as school children. Parents role in protecting school children from sex abuse are by supervising, giving advise, providing early religious education, becoming a good role model, and creating a conducive atmosphere in family. The aim of the research was to describe parents role in protecting school children from sex abuse. The research design was a descriptive approach. The population was 578 parents of students in SDN Sanawetan 02 Blitar city. The sample was 58 parents taken by quota sampling. The data collection was done by door to door on July 6 – August 14, 2015. The result showed that 69% (40 parents) less involved, 28% (26 parents) fair involved, and 3% (2 parents) actively involved. Factors affecting less involved parents was culture, education, and job. The role of Less involved parents showed by less interaction with the school, didn’t give information on sex abuse, didn’t accustom child to be extrovert, and avoid fighting in front of children. Increasing parents concern to children could decrease sex abuse of school children case.